Deciding for imperilled newborns: medical authority or parental autonomy? - McHaffie, H; Laing, I; Parker, M; McMillan, J (2001)
The ethical issues around decision making on behalf of infants have been illuminated by two empirical research studies carried out in Scotland. In-depth interviews with 176 medical and nursing staff and with 108 parents of babies for whom there was discussion of treatment withholding/withdrawal, generated a wealth of data on both the decision making process and the management of cases. Both staff and parents believe that parents should be involved in treatment limitation decisions on behalf of their babies. However, whilst many doctors and nurses consider the ultimate responsibility too great for families to carry, the majority of parents wish to be the final arbiters. We offer explanations for the differences in perception found in the two groups. The results of these empirical studies provide both aids to ethical reflection and guidance for clinicians dealing with these vulnerable families. They demonstrate the value of empirical data in the philosophical debate.